Evaluasi Efisiensi Anggaran Pembangunan Jalan dan Jembatan Bypass Mamminasata Segmen I dan II Dengan Pendekatan Cost Performance Index (CPI) - Styaji, Hary; Sobirin , Mohamad (Syntax Corporation, 2025)
This study analyzes the budget efficiency of the Mamminasata Bypass Road and Bridge Construction Project Segment I and II using the Cost Performance Index (CPI) from the Earned Value Management (EVM) method. This project has a contract value of IDR 139.90 billion and an implementation period from November 2022 to March 2024. The data used is secondary data in the form of monthly progress reports, financial statements, and contract documents. The parameters analyzed included Planned Value (PV), Earned Value (EV), Actual Cost (AC), CPI, Cost Variance (CV), and Schedule Performance Index (SPI). The results showed an average CPI value of 0.99, which indicates excellent budget efficiency with a cost overrun of only 0.99%. CPI fluctuations over the course of the project are relatively minimal, indicating the stability of cost performance. Multiple regression analysis identified four significant factors that affect budget efficiency, namely soil conditions (β = -0.412, p = 0.005), design changes (β = -0.289, p = 0.010), volume changes (β = -0.198, p = 0.043), and price escalation (β = -0.367, p = 0.001), with the regression model having R² = 0.847. A comparison of budget efficiency between Segments I and II showed no significant difference (p-value = 0.682), with Segment I CPI 0.990 and Segment II 0.989. This study contributes to the implementation of EVM in road projects in Indonesia and recommends the use of CPI as an effective monitoring tool for controlling the cost of infrastructure projects.